(untitled) - Singhvi, L. M. (New Delhi, 1991)
This entry about Freedom on trial has been published under the terms of the Creative Commons Attribution 3.0 (CC BY 3.0) licence, which permits unrestricted use and reproduction, provided the author or authors of the Freedom on trial entry and the Encyclopedia of Law are in each case credited as the source of the Freedom on trial entry. Please note this CC BY licence applies to some textual content of Freedom on trial, and that some images and other textual or non-textual elements may be covered by special copyright arrangements.
Keywords: Luật pháp,Constitutional law; Ấn Độ,India